Efficacy and safety of Qiangli Dingxuan tablet combined with amlodipine besylate for essential hypertension: a randomized, double-blind, placebo-controlled, parallel-group, multicenter trial - Lin, Jianguo; Wang, Qingqing; Zhong, Dongsheng; Zhang, Jinju; Yuan, Tianhui; Wu, Hui; Li, Bin; Li, Shuangdi; Xie, Xiaoliu; An, Dongqing; Deng, Yue; Xian, Shaoxiang; et al. (Frontiers in Pharmacology, 2023)
Background: Hypertension, a major cardiovascular risk factor, severely impacts patients' quality of life. Qiangli Dingxuan tablet (QDT) is a formally approved Chinese patent medicine, which has been widely used as an adjunctive treatment for hypertension. This study aimed to investigate the antihypertensive efficacy and safety of QDT combined with amlodipine besylate in patients with essential hypertension.In this randomized, double-blind, placebo-controlled, parallel-group, multicenter trial conducted in China, patients diagnosed with grade 1 to 2 essential hypertension were randomly assigned in a 1:1 to the treatment of QDT or placebo for 12 weeks, alongside their ongoing treatment with amlodipine besylate. The primary outcome was the change in office blood pressure (BP) from baseline to 12 weeks. In addition, safety analysis included the assessment of vital signs and laboratory values.. This is a provisional file, not the final typeset article Results: At baseline, 269 patients were randomly assigned to the QDT group (n=133) or the placebo group (n=136), and there were no significant differences in baseline characteristics between the two groups. The primary outcome based on the full analysis set from baseline to 12 weeks showed that the mean difference in the change of office systolic BP reduction between the two groups was 6.86 mmHg (95%CI, 4.84 to 8.88, P<0.0001), for office diastolic BP, the mean difference in the change of office diastolic BP reduction between the two groups was 4.64 mmHg (95%CI, 3.10 to 6.18, P<0.0001). In addition, traditional Chinese medicine symptom scores were significantly decreased in the QDT group compared with the placebo group. No severe adverse events attributable to QDT were reported.The combination of QDT and amlodipine besylate demonstrates superior efficacy compared to amlodipine besylate monotherapy in the management of essential hypertension. QDT shows potential as an adjunctive treatment for essential hypertension. However, further rigorous clinical trials are warranted to validate these findings.